AGRI-ENVIRONMENTAL LEGISLATIVE FRAMEWORK IN SERBIA IN LIGHT OF THE HARMONISATION WITH EU LAW - Jovanić, Tatjana (Economics of Agriculture, 2013)
Economic sanctions, production and economic drop, as well as impoverishment have significantly reduced capabilities of the state for investment in environmental protection, but as well environmental concerns of agricultural producers. However, compliance with mandatory standards and rules forming the corpus of agri-environmental measures and principles of good agricultural practice are an important step towards preservance of the environment and care about health of humans, plants and animals. On the other side, it is an important prerequisite for Serbian exports of agricultural products. In addition from mandatory rules, which are also relevant for fulfillment of the duty of cross-compliance for producers receiving direct payments, agri-environmental incentives as voluntary commitments of producers to provide a higher level of environmental protection are particularly welcome, but are hardly possible to give rise in the short term. The Paper gives a short overview of agri-environment policy in the EU and is mostly focused on mandatory rules setting duties and responsibilities of agricultural producers and issues related to approximation of Serbian legislative framework with the EU.